Eksistensi dalam Mengoptimalisasikan Pelaksanaan Proses Dismissal dan Pemeriksaan Persiapan di Pengadilan Tata Usaha Negara: Prosedur Dismissal, PTUN, Gugatan - Sabila Riri (Jurnal Penelitian Multidisiplin, 2023)
The State Administrative Court is an application whose formation is intended as a special court to assess, decide and resolve state administrative disputes. One of the features of the administration of this judiciary compared to other courts is the examination of each claim by the Chief Justice before the case is forwarded to the Panel of Judges. The lawsuit for examination by the Chief Justice is called the dismissal process or dismissal procedure. Even though there are juridical and implementation constraints, this does not mean that the process for dismissal and preparation for dismissal cannot be carried out through an electronic hearing. Then, this instrument which is still relevant is applied. The authority of the Chief Justice of the dismissal procedure has increased the authorities for justice and the length of the road to fight for justice so that the existence of the State Administrative Court as an institution that indirectly exercises judicial control will be maximized. With this, the government will feel that it is continuously being watched by its people, as well as the willingness to make corrections or legal resistance to decisions by the TUN Agency or Officials that are considered detrimental to society.